Designing a Sustainability Assessment Framework for Peruvian Manufacturing Small and Medium Enterprises Applying the Stakeholder Theory Approach - Córdova-Aguirre, L.J. (2024)
Among the main obstacles affecting the competitiveness of Peruvian Small and Medium Enterprises (SMEs) are poor strategic planning and incipient use of management control systems that support the integration of sustainable practices for the growth of the organization. Not considering sustainability in the strategy and management control systems of Peruvian SMEs can jeopardize their stability and growth, as they are part of the supply chain of large companies that look for suppliers that comply with sustainability standards. Since manufacturing SMEs play a vital role in the economies and social welfare of countries, providing them with appropriate management tools to evaluate the sustainable performance of their activities is urgent to assure their survival. Thus, the aim of this study is to design a holistic sustainability assessment framework that enables Peruvian manufacturing SMEs to evaluate the full integration of sustainability into their business strategy and the creation of value for each stakeholder. Based on the gaps found in the literature review, a conceptual assessment framework was designed, then a multiple-case study was conducted in three Peruvian manufacturing SMEs in the plastic sector, and the data obtained were used to deploy the proposed conceptual assessment framework.